سیرت محمدی :حضرت علی ابن ابی طالب کے خطبات کا ایک مطالعہBiography of the Holy Prophet: A Study of the Sermons of Hazrat Alī Ibn Abī Tālib (Al-Qamar, 2022)
Allah Almighty has made the life of the Holy Prophet Mohammad (PBUH) a role model for the betterment and reforming of society. He (PBUH) delivered the message of Allah to the world and saved them from the torment of Allah, teaching them to worship and love one God. He gave a system of life that leads humanity to peace and security and is a total mercy for mankind. All his life he treated God's creatures with kindness and mercy. His mercy was not only for the believers, but also for the disbelievers. Therefore, in this article, the biography of the Holy Prophet (PBUH) will be narrated from Nahjul Balagha.  Because Hazrat Ali (AS) has mentioned the good morals of the Holy Prophet (PBUH) in Nahj al-Balaghah as well as somewhere he has described his virtues. In the same way, somewhere he has stated the purpose of enlightenment and somewhere he has shed light on patience and courage of the Holy Prophet (PBHU). Somewhere he has described asceticism and piety, somewhere he has mentioned his benevolence, somewhere he has mentioned a physician for the healing of the sick. Therefore, in this article, the biography of the Holy Prophet (sws) will be narrated from Nahjul Balagha along with Qur'an and Hadith.
Keywords: Moral; Patience; Bravery; Piety; Wisdom